The Impact of the Secondhand Clothing Import Ban Policy on the Trade of Used Garments - Amelia, Natasya Aretha; Purnawarman, Andi (LifeSciFi, 2025)
This study investigates the impact of the government’s import ban on used clothing on the secondhand clothing trade. The research seeks to understand how the policy has influenced local trading activities, market dynamics, and consumer behavior. The primary objective of this study is to analyze and describe the socio-economic effects resulting from the implementation of the used clothing import ban, with a particular focus on shifts within the local second-hand clothing market. To achieve this, the study employs a descriptive qualitative approach. Data collection methods include direct field observations, unstructured interviews with traders and consumers, and literature reviews from relevant academic sources and policy documents. This methodological framework allows for an in-depth exploration of the issue from multiple perspectives. The results show that while the import ban has not fully halted secondhand clothing trade, it has contributed to a noticeable slowdown. There has been a gradual reduction in the number of active thrift traders, alongside a modest but growing consumer shift toward new, locally manufactured garments often viewed as more hygienic. Additionally, local garment producers have reported stable or increased demand during certain seasons. The policy has begun to influence market behavior, though its effectiveness remains partial and ongoing.